Estudo da influência da quantidade de lodo na produção de biogás em reator UASB tratando esgoto doméstico - Déborah de Freitas Melo (2015)
Treatment of domestic raw sewage through anaerobic leads to the formation of biogas, which can be harnessed as energy. However, the stations find it difficult to understand the behaviour of the production, so as to estimate how much biogas is produced and what the characteristics of that gas. Another operational difficulty is related to the start-up the reactors, requiring the presence of microorganisms adapted to the effluent. In order to deepen our knowledge of this gap, this research was developed to interpret the behaviour of methane production, both within the gas and liquid phases in a UASB reactor, evaluating the influence of the amount of sludge inside the reactor. For the first specific objective, there were two cycles of self inoculation to assess the evolution of this biomass to methane production. The results show that self-inoculating a UASB reactor leads to satisfactory yields close to day 60, with productions of biogas of around 113 NL/d, and a methane concentration of about 68%v/v. Methane concentrations dissolved in the effluent were about 17 mg/L, which represented about 30% of the methane produced. Was obtained in the inoculation cycles of self loading a biological 0.29 gCOD/gSTV.dia. The second specific objective focused on varying the amount of sludge reactor in two phases: one tending to maximum mass sludge reactor (phase 1) and the other, tending to minimum mass (phase 2). The results showed greater variability in stage 1, for both daily volume production, and for the methane dissolved in the effluent. The biogas production in phase 1 was 114 NL/day and in phase 2 of 87 NL/day, significantly lower than that of phase 1. The methane concentration in the biogas were 69% v / v for Phase 1 and 63% v / v to phase 2. The dissolved methane in the effluent showed median concentrations of 22 mg/L for both phases. The methane fractions in the gaseous phase and the liquid phase showed significant differences between the phases. The methane fractions in the gaseous phase and the liquid phase showed no significant differences between the phases. The sludge age was 86 days in phase 1 and 55 days in phase 2. It is understood that since the establishment of the minimum mass needed in the reactor, a sludge/biomass increase is not significant increase in the quality of the biogas generated. However, periodic discharges sludge in the reactor when working close to the minimum mass, promote the reduction of sludge age and become less concentrated. Thus, it is understood that the sludge periodic discharges would be interesting only for reactors working close to their maximum mass.